INCORPORACION DE UN NUEVO MODELO DE JUSTICIA RESTAURATIVA PARA ADOLESCENTES EN CONFLICTO CON LA LEY PENAL QUE PROTEJA SUS GARANTIAS Y DERECHOS, POR LO QUE SE HACE NECESARIA INTRODUCIR UNA REFORMA AL LIBRO IV DEL CÓDIGO ORGANICO DE LA NIÑEZ Y ADOLESCENCIA - MEDINA LIMA, MARIANELA LUCIA (2016)
The human being to fulfill its objectives was organized in Society, the same is governed by a government (State) and to protect the organization, have created punitive about standards, which are mandatory for all. Being raped these rules, we proceed to a punitive punishment by the state once the person convicted, and is issued a statement, which must fulfill a social rehabilitation center. This penal system applies to both adults and minors. The prison system in our country is in chaos, overcrowding and lack of political rehabilitation and social reintegration is one of the evils it has. In addition, the prison crisis that occurs influences the personality of the offender, because instead of receiving a discharge, these become crime schools. This problem is taxed with juvenile delinquency when he is imprisoned. The advantage of implementing restorative justice for Juvenile Offenders is that the offender recognizes the harm caused to the victim, to demonstrate the possibility of correction and to assume the consequences of their actions, thus repairing the damage caused to the victim, reintegration of the adolescent, like the non-recurrence of the same. Regarding my issue raised about the need for a reform of the Organic Code of Childhood and Adolescence incorporating a new model of 14 restorative justice for juveniles in conflict with their prohibited conduct established by law, in some cases as felonies, requiring coercive sanction directly. But that Ecuadorian legislation currently in our socio- educational measures for adolescent offenders apply this to be a central issue as the socio- educational measures currently applicable not guarantee that the juvenile offender not engaging in unethical or illegal behavior, after serving his judgment, because in some circumstances repair the damage caused is rather help the criminal recidivism does not have the highest percentage growth. From this perspective I point to the inadequacy of the current legislation to prevent the commission of crimes by young offenders.